Innovation of a Model of Field Experience Practice-Based Lesson Study (THLS) to Enhance Pre-Service Science Teacher Research Skills - Ilhami, Aldeva; susilawati, susilawati; Yusrianto, Edi; Lokollo, Lita; Fadilah, Muhyiatul; Handrianto, Ciptro (Journal of Education Reseach and Evaluation, 2023)
Teacher Training Institutions (LPTK) have emerged as an area for attention in arranging professional teacher candidates and possess high competitiveness for achieving the Sustainable Development Goals (SDGs) 2030. In this regard, teacher candidates will conduct Field Experience Practice (PPL) to implement theoretical understanding with practical experience to strengthen competences. This study was carried out to analyze the validity, practicality, and effectiveness of the Triple Helix model-Based Lesson Study (THLS) of PPL. Research subjects consisted of lecturers, teachers, students, and PPL managers at the university. This study conducted through the Plomp development model, the research instrument included a questionnaire, test, and observation sheet. Data were analyzed using the miles-huberman analysis model. The results showed that the level of validity and practicality of PPL model is considered very good with the percentage 92%. The model is effective showed there is a difference in the research skills between pre service science teacher who followed the THLS PPL model and the common PPL model. The THLS PPL model is considered suitable for technical use to enhance the research skills of prospective teachers.